2019
DOI: 10.1111/vsu.13192
|View full text |Cite
|
Sign up to set email alerts
|

Partial arytenoidectomy in 14 standing horses (2013–2017)

Abstract: Objective: To report our experience with partial arytenoidectomy in sedated standing horses. Study design: Retrospective study. Animals: Fourteen client-owned adult horses. Methods:The medical records (2013-2017) of horses treated with unilateral partial arytenoidectomy while standing and sedated were reviewed. Demographics, endoscopic findings, previous treatments, and outcome after surgery were investigated and recorded. Results: Thirteen horses had unilateral left-sided recurrent laryngeal neuropathy (RLN) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Higher levels of air mixing and eddy formation are strongly correlated with severity of obstruction ( 29 , 30 ). This provides further evidence that revisional surgery may be worthwhile in cases with postoperative noise and poor performance as has been suggested clinically ( 3 , 32 ). Another consistent feature of the PA was the presence of negative pressure and high velocity inside the left wall of the larynx.…”
Section: Discussionsupporting
confidence: 71%
“…Higher levels of air mixing and eddy formation are strongly correlated with severity of obstruction ( 29 , 30 ). This provides further evidence that revisional surgery may be worthwhile in cases with postoperative noise and poor performance as has been suggested clinically ( 3 , 32 ). Another consistent feature of the PA was the presence of negative pressure and high velocity inside the left wall of the larynx.…”
Section: Discussionsupporting
confidence: 71%
“…Airway contamination is one of the most serious complications faced by clinicians. Clinical signs such as dysphagia and dyspnea have been described in horses after partial arytenoidectomy (6,13). Speirs reported that 36% of horses showed dysphagia after partial arytenoidectomy (13); however, horses showing severe dysphagia after partial arytenoidectomy have been reported less frequently in recent studies (1,6,8,10,15).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical signs such as dysphagia and dyspnea have been described in horses after partial arytenoidectomy (6,13). Speirs reported that 36% of horses showed dysphagia after partial arytenoidectomy (13); however, horses showing severe dysphagia after partial arytenoidectomy have been reported less frequently in recent studies (1,6,8,10,15). Recently, Radcliffe, et al (10) reported airway contamination in horses 3 months after partial arytenoidectomy and laryngoplasty; the apparent inflammatory changes in tracheobronchial fluid indicated that both surgeries caused airway contamination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations